Association of Serum Low Density Lipoprotein Cholesterol and High Density Lipoprotein Cholesterol with Hypertension in Adult Female - Mahmuda, Sayeeda; Yeasmin, Nahid; Abira, Mahmuda; Rahman, Farhana; Hasan, Mahmudul; Rabbani, Rukhshana; Yeasmin, Shahanara; Habib, Tamanna Binte; Das, Konica (Bangladesh Critical Care Journal, 2018)
Background: Hypertension is a chronic and debilitating disease. Its complications are increasing all over the world, leading to life threatening medical problems like cardiovascular diseases, stroke and end stage renal diseases. An association between hyperlipidemia and hypertension has been identified. Objectives: The study was carried out to observe the association of serum low density lipoprotein cholesterol and high density lipoprotein cholesterol level with hypertension in adult female subjects. Method: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January 2011 to December 2011. A total number of sixty female subjects were selected with age ranging from30 to50 years. Among them 30 female subjects with hypertension were included from out-patient department of Medicine, Dhaka Medical College Hospital, Dhaka as study group(B) and 30 apparently healthy females were taken as control group(A) for comparison. Estimation of serum fasting serum low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C) levels were done by enzymatic method in the Department of Physiology, Dhaka Medical College Dhaka in both groups. Systolic blood pressure and diastolic blood pressure of all participants were recorded by standard method. Data were analyzed by Unpaired Student’s- test and Pearson's correlation co-efficient (r) test as applicable. Result: The value of fasting serum LDL level was significantly higher in subjects with hypertension than those of control. Fasting serum HDL level was significantly lower in subjects with hypertension in comparison to control. In subjects with hypertension fasting serum LDL-C showed positive correlation with systolic and diastolic blood pressure and serum HDL-C showed negative correlation with systolic and diastolic blood pressure. Conclusion: Present study revealed that systolic and diastolic blood pressure has positive relationship with low density lipoprotein cholesterol (LDL-C) and negative relationship with high density lipoprotein cholesterol (HDL-C) levels. Bangladesh Crit Care J September 2018; 6(2): 74-79